Aspek Hukum Peranan Wali Amanat dalam Penerbitan Obligasi Syariah Mudharabah - Dita Febrianto (Universitas Bandar Lampung (UBL), 2010)
The Sharia bonds arise in connection with the development of Sharia financialinstitutions, such as Sharia insurance, Sharia pension funds and Sharia mutual fundsin need of alternative investment. National Sharia Board Decision (DSN) No.32/DSN-MUI/IX/2002 about Bonds and the National Sharia Board Decision (DSN) No.33/DSN-MUI/IX/2002 about Sharia Mudharabah Bonds, Sharia Bonds provides that asa long-term that are debt, with obligation to payed interest at a certain period andrepay principal. So, Sharia Mudharabah Bonds in principle being is debt letters withEmiten obligations of the profit sharing to investors.